Highly Narrowband Photomultiplication Type Organic Photodetectors - Wang, Wenbin; Zhang, Fujun; Du, Mingde; Li, Lingliang; Zhang, Miao; Wang, Kai; Wang, Yongsheng; Hu, Bin; Fang, Ying; Huang, Jinsong (Nano letters, 2017)
Filterless narrowband response organic photodetectors (OPDs) present a great challenge due to the broad absorption range of organic semiconducting materials. The reported narrowband response OPDs also suffer from low external quantum efficiency (EQE) in the desired response window and low rejection ratio. Here, we report highly narrowband photomultiplication (PM) type OPDs based on P3HT:PC71BM (100:1, wt/wt) as active layer without an optical filter. The full width at half-maximum (fwhm) of the PM-type OPDs can be well retained less than 30 nm under different biases. Meanwhile, the champion EQE and rejection ratio approach 53 500% and 2020 at −60 V bias, respectively. The small fwhm should be attributed to the sharp absorption edge of active layer with small amount of PC71BM. The PM phenomenon is attributed to hole tunneling injection from the external circuit assisted by trapped electron in PC71BM near the Al electrode under light illumination. These highly narrowband PM-type OPDs should have great potential applications in sensitively detecting specific wavelength light and be blind to light outside of the desired response window.